Penentuan Daya Jerap Karbon Aktif Dari Polong Akasia Terhadap Ion Cr(VI) - Run Bunga Dewi; Yusnimar Yusnimar; Rozzana Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Activated carbon which has a high adsorption capacity for the adsorbate. Activated carbon can be produced from materials containing carbon or charcoal was treated in a certain wayto gain more surface area. The research goal was to process acacia pod into a activated carbon and determine the adsorption power of the ion Cr (VI). The dried acacia pod was carbonated in a sealed drum to produced charcoal / carbon. Charcoal was crushed into aparticle size of 100 mesh. Charcoals with a size of 100 mesh were activated physically and chemically. The activation process of carbon physically carried out at a temperature of 200,300 and 400 ºC. While chemically, activated carbon was done by used Na2CO3 as an activator. Carbon/charcoal was soaked in a solution of Na2CO3 for 24 hours. Furthermore, itwas separated from the solution of Na2CO3 and dried at a temperature of 105 ºC. Activated carbon obtained both physically and chemically characterized to determine such as ashcontent, moisture content and adsorption power of the metilen blue solution and Cr(VI) in solution. The results showed that the carbon which activation under a temperature of 400 ºCwas the best activated carbon has a water content of 1.5%, ash content of 2.3%, adsorption power of the metilen blue 99,81% and the adsorption power of the ion Cr(VI) 87,72%.Keywords: Adsorption, Physics Activation, Chemical Activation, Activated Carbon and acacia pod